Taxonomic notes on Iris ser. Lacteae (Iridaceae) with typifications of fifteen names and one new combination - Boltenkov, Eugeny V. (Phytotaxa, 2018)
Nomenclatural and taxonomic notes, discussed in the article, are based on the result of a taxonomic revision of Iris ser. Lacteae, which is currently underway. This series includes 3 species: I. lactea, I. oxypetala, and I. tibetica. The protologues, relevant literature, and the types of all the published names belonging to the series have been reviewed. Iris lactea, in addition to the type form with milky-white flower colour, is represented by I. lactea f. biglumis, being the most widely distributed form with light-blue or pale-purple flower colour, and by I. lactea f. chrysantha, showing yellow inner perigone segments. Both taxa are typified here, and a new combination is proposed. The typification of the following names, all synonyms of either I. lactea f. biglumis (I. caricifolia, I. doniana, I. ensata var. grandiflora, I. fragrans, I. haematophylla, I. iliensis, I. longifolia, I. longispatha, I. pabularia, I. pallasii, and I. triflora) or I. oxypetala (I. moorcroftiana and I. pallasii var. chinensis) is also discussed. A list of accepted names within I. ser. Lacteae and their synonyms, including an identification key, is provided.